Strategi Komunikasi Berbasis Kecerdasan Buatan (AI) dalam Mempromosikan Nilai Pancasila di Era Digital - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Imam Islamuddin; Nur Fadila Pramesti; Ibrahim Ausen; Shiva Jea Nezia Aora (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The challenge of promoting Pancasila values in the era of Artificial Intelligence (AI)-based digitalization within the field of communication is the main focus of this study. The core issue addressed is how AI-based communication strategies can be utilized to strengthen Pancasila values amid the rapid development of information technology. This research adopts a qualitative approach using a literature review method, collecting data from relevant academic journals and books. Through content analysis, the study identifies effective communication strategies, ethical challenges, and the potential of AI in disseminating national values. The results show that AI plays a significant role in promoting Pancasila values through technologies such as educational chatbots, intelligent content distribution algorithms, and social media sentiment analysis systems. However, there are also challenges to address, including algorithmic bias, misuse of AI, and data security concerns. The study concludes that the ethical and well-directed use of AI, based on Pancasila principles, can be a strategic solution to reinforce national identity and youth character in the digital era.